1991
DOI: 10.1182/blood.v78.3.635.635
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of early hematopoiesis by tumor necrosis factor-alpha is followed by inhibition of granulopoietic differentiation and proliferation

Abstract: We have previously shown that tumor necrosis factor-alpha (TNF alpha) strongly potentiates interleukin-3 (IL-3)-induced short-term proliferation of human CD34+ hematopoietic progenitor cells (HPC). Using longer term cultures of CD34+ HPC, we demonstrate here that this initial potentiation ceases after 10 to 12 days; whereupon TNF alpha displays inhibitory effects. Thus, TNF alpha was found to inhibit cells of granulocytic affiliation while it potentiates the development of maturing cells of the monocytic linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
1
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 49 publications
3
20
1
1
Order By: Relevance
“…The stimulating role of TNF on CFU-GEMM growth was unexpected. For CFU-GEMM from CD34 cord blood cells Caux et al (1991) found TNF had an inhibitory effect, although with higher concentrations of TNF than in our assay. TNF is a pleiotrophic cytokine and its effect might depend on dose and growth factor combination.…”
Section: Discussioncontrasting
confidence: 53%
“…The stimulating role of TNF on CFU-GEMM growth was unexpected. For CFU-GEMM from CD34 cord blood cells Caux et al (1991) found TNF had an inhibitory effect, although with higher concentrations of TNF than in our assay. TNF is a pleiotrophic cytokine and its effect might depend on dose and growth factor combination.…”
Section: Discussioncontrasting
confidence: 53%
“…39 This proliferative effect was revealed to be short term; after initial proliferation, TNF-a inhibited the in vivo differentiation of granulocytic cells while driving the development of maturing monocytic cells. 40 More recently, Welner et al 28 demonstrated that reduced in vivo B-cell production from lymphoid precursors in response to TLR9 ligation was suppressed by TNF-a, while DC production observed under the same conditions was independent of TNF-a. Taken together, this evidence suggests that although TNF-a can affect the generation of BMDCs, other growth and differentiation factors may be required to generate all the effects observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Such a hypothetical mechanism could be mediated by the secretion of TNF-a 30,31 by activated macrophages. This cytokine is primarily synthesized by macrophages 32 and known to induce programmed cell death in a variety of target cells 33 , especially haemopoietic progenitor cells [34][35][36][37] . Interestingly, raised serum levels of TNF-a have been described in various inflammatory conditions 30 , in particular rheumatoid arthritis 38 , MDS [39][40][41][42][43][44] and AIDS [45][46][47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%